12 rounds 2 : reloaded [videorecording (DVD)] - Reiné, Roel; Orton, Randy; Busby, Cindy; Markinson, Brian (Twentieth Century Fox Home Entertainment, 2013)
Paramedic Nick Malloy is plunged into a deadly game of cat and mouse when he receives a terrifying phone call from a vengeful psychopath connected to his past. The maniac threatens to unleash a murder spree unless Nick can complete a series of twelve challenges without involving the cops or missing a single deadline.